2018
DOI: 10.1002/ecs2.2066
|View full text |Cite
|
Sign up to set email alerts
|

Livestock and the functional habitat of vicuñas in Ecuador: a new puzzle

Abstract: Abstract. Whether interactions between wildlife and livestock are competitive or facilitative is context dependent. Intermediary factors that explain how context (seasonal or regional characteristics of the ecological community) affects these interactions are rarely reported. We compared activity time and density in vicuñas (Vicugna vicugna) introduced into the Chimborazo Faunal Production Reserve (CFPR), Ecuador, to describe how they interact with livestock. We compared vicuña density in wetlands and uplands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
(152 reference statements)
0
7
0
Order By: Relevance
“…More research is certainly needed to confirm the trends found in this study, as our limited sample size and lack of seasonal variation in the data makes it hard to generalize results on a wide scale. Moreover, previous research has shown that in grassland ecosystems ungulates and livestock coexistence is possible [ 54 , 55 , 68 , 69 ]. It may be important to focus research on better understanding the livestock species specific stocking rates that benefit producers without compromising the future of wild ungulate populations in forest ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…More research is certainly needed to confirm the trends found in this study, as our limited sample size and lack of seasonal variation in the data makes it hard to generalize results on a wide scale. Moreover, previous research has shown that in grassland ecosystems ungulates and livestock coexistence is possible [ 54 , 55 , 68 , 69 ]. It may be important to focus research on better understanding the livestock species specific stocking rates that benefit producers without compromising the future of wild ungulate populations in forest ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…This protected area is located in Chimborazo, Bolivar and Tungurahua provinces, created specifically for Vicuña conservation. The census carried out during 2000-2016 showed an exponential annual growth rate of 11% reaching 7,185 individuals in 2016 (MAE 2016), suggesting that neither predation nor carrying capacity are currently regulating the species in the area (McLaren et al 2018).…”
Section: Populationmentioning
confidence: 99%
“…Exploitation competition occurs due to alteration to forage quantity and/or quality (Ranglack et al, 2015;Kimuyu et al, 2017;Keesing et al, 2018), fire regimes and vegetation structure (Kimuyu et al, 2014;Hempson et al, 2017;Odadi et al, 2017a), water availability (Connolly et al, 2021), predation risk (Ng'weno et al, 2019), and/or disease transmission (Keesing et al, 2018). However, moderate levels of grazing by livestock and wildlife can also improve pasture quality and facilitate coexistence in certain agro-ecological and climatic contexts (Brown et al, 2010;Odadi et al, 2011;McLaren et al, 2018;Young et al, 2018).…”
Section: Introductionmentioning
confidence: 99%